2020
DOI: 10.3390/ma13204567
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue-Induced Evolution of AISI 310S Steel Microstructure after Electron Beam Treatment

Abstract: Research was carried out to explore the effect of pulsed electron beam irradiation on the behavior of structure and phase state in AISI 310S steel exposed to high-cycle fatigue. A 2.2 times increase in the fatigue life of samples irradiated by electron beams was revealed. The outcomes of scanning and transmission electron microscopic studies suggest the most probable reason for the fracture of steel samples irradiated by a high-intensity electron beam to be microcraters originating on a treated surface and act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 37 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Moreover, the surface quality parameters, such as roughness, accuracy, physical, and mechanical parameters were high enough, and their values met the technical requirements for the working surfaces of hydrocylinder liners. However, these parameters were not optimal for the "metal-rubber" coupling that performs relative movements [29][30][31][32][33][34][35].…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Moreover, the surface quality parameters, such as roughness, accuracy, physical, and mechanical parameters were high enough, and their values met the technical requirements for the working surfaces of hydrocylinder liners. However, these parameters were not optimal for the "metal-rubber" coupling that performs relative movements [29][30][31][32][33][34][35].…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…The authors of [7,8] have studied the possibility of controlling the structure and properties of tool steels with electron beam treatment technology. They concluded that the mechanical characteristics of the samples were greatly improved after applying the treatment technology due to the formation of a finer microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…В современных исследованиях продемонстрированы результаты применения электронных пучков совместно с другими технологиями, такими как электродуговая и электроконтактная проволочная наплавка [10], модификация поверхностных слоев аддитивно изготовленных изделий [11], поверхностное легирование [12], комбинация применения плазменных потоков с последующим низкоэнергетическим сильноточным электронным пучковым воздействием [13]. В результате обработки электронными пучками высокой плотности на поверхности обрабатываемых сталей и сплавов происходит высокоскоростная рекристаллизация, отжиг, пластическая деформация и улучшение топографии поверхности [14]. В работе [15] отмечается перспективность обработки высокоточным электронным пучком с целью удаления дефектов высокоэнтропийного сплава (ВЭС) NiCoCrAlYSi, полученного лазерной наплавкой.…”
Section: Introductionunclassified